Simultaneous monitoring and quantification of Melampsora allii‐populina and Melampsora larici‐populina on infected poplar leaves using a duplex real‐time PCR assay. (26th June 2015) - Guinet, C.; Boutigny, A. L.; Vialle, A.; Hamelin, R. C.; Frey, P.; Ioos, R.
Abstract : The rust fungi Melampsora larici‐populina (Mlp) and Melampsora allii‐populina (Map) are the main phytosanitary constraints for commercial poplar cultivation in Europe. Although Mlp is more aggressive and prevalent than Map, the two species may co‐infect the same poplar tree or even the same poplar leaf, making the epidemiological surveys of each species difficult to achieve. In this study, a new duplex real‐time PCR assay targeting each species was developed, based on single‐copy genes. This test proved to be specific, inclusive and was successfully used to detect and quantify each species, starting from urediniospore samples or directly from infected poplar leaves, with or without visible symptoms. This new molecular tool was also assessed for comparative studies of time‐course infection experiments on artificially inoculated poplar leaf discs. These studies showed that the growth dynamics of Map were significantly slower when the two species were co‐inoculated on the same leaf disc, confirming that Map is less aggressive than Mlp.